If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 15 = 83 Reorder the terms: 15 + 4x = 83 Solving 15 + 4x = 83 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 4x = 83 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 83 + -15 4x = 83 + -15 Combine like terms: 83 + -15 = 68 4x = 68 Divide each side by '4'. x = 17 Simplifying x = 17
| -7-2(9z-1)=9(3z-4)-4 | | -7-2(9z-1)=9(3z-4)4 | | 41-7x=2x+16 | | 5-10x=13-17x | | -8-8(2y+1)=3(y+3)-2 | | -4u+1=-u-17 | | 3(6x+1)-2(7x-4)=43 | | x-8x+2x-6x= | | -8v+12=-2(4v-6) | | 2p-5=8+2p | | 99-2x=5x+8 | | -(z+7)+(6z+1)=-4(z+1) | | 6.1v-1=2.8v+2.3 | | 6x-5=19-2x | | 5w+5=-6w+16 | | (3m^3y^2+6m^4-2my)(2m+y)= | | 99-6x=13-9x | | 6x-4=(x+3) | | -w-1=6w+20 | | y-6=-5(x-0) | | 6x^2=-12x-4 | | 5x-2y=-9 | | -5z+8=2(2z-5) | | (5x+1)2=7 | | 23-5(x+10)=-12 | | 4x-5=2x-9 | | 8-8=10x+5x | | 5-x=(-7) | | 8x+1=4x+9 | | 6u-16=-2(-3u+8) | | 9-9x=194-44x | | 5x+12=-72-9x |